Size-controlled synthesis of Fe3O4 magnetic nanoparticles in the layers of montmorillonite - Kalantari, Katayoon; Ahmad @ Ayob, Mansor; Shameli, Kamyar; Hussein, Mohd Zobir; Khandanlou, Roshanak; Khanehzaei, Hajar (Hindawi Publishing Corporation, 2014)
Iron oxide nanoparticles (Fe3O4-NPs) were synthesized using chemical coprecipitation method. Fe3O4-NPs are located in interlamellar space and external surfaces of montmorillonite (MMT) as a solid supported at room temperature. The size of magnetite nanoparticles could be controlled by varying the amount of NaOH as reducing agent in the medium. The interlamellar space changed from 1.24 nm to 2.85 nm and average diameter of Fe3O4 nanoparticles was from 12.88 nm to 8.24 nm. The synthesized nanoparticles were characterized using some instruments such as transmission electron microscopy, powder X-ray diffraction, energy dispersive X-ray spectroscopy, field emission scanning electron microscopy, vibrating sample magnetometer, and Fourier transform infrared spectroscopy.